2014
DOI: 10.1097/ftd.0b013e3182a8997c
|View full text |Cite
|
Sign up to set email alerts
|

Determination by LC–MS/MS of Colistins A and B in Plasma and Ultrafiltrate From Critically Ill Patients Undergoing Continuous Venovenous Hemodiafiltration

Abstract: Two simple methods for the simultaneous determination of colistins A and B have been developed and validated. Their application in the clinical setting demonstrates that CVVHDF treatment lasting 48 hours produces a relatively constant and efficient removal of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…Taken together, these findings suggest that CMS clearance may be filter limited, while colistin CRRT clearance depends on blood flow. Two other studies both using 9-MU daily maintenance doses and a blood flow of 120 ml/min (comparable to the present study) in seven and four patients undergoing CRRT (11,24) showed colistin CRRT clearances of about 0.7 liter/h, which compared to our findings. For daily clinical practice, we therefore suggest starting CMS in patients that are undergoing CVVHD using low blood flows with a loading dose of 9 MU and a maintenance dose of 3 MU every 8 h (independent of body weight), so that therapeutic colistin concentrations have a high likelihood of being achieved.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Taken together, these findings suggest that CMS clearance may be filter limited, while colistin CRRT clearance depends on blood flow. Two other studies both using 9-MU daily maintenance doses and a blood flow of 120 ml/min (comparable to the present study) in seven and four patients undergoing CRRT (11,24) showed colistin CRRT clearances of about 0.7 liter/h, which compared to our findings. For daily clinical practice, we therefore suggest starting CMS in patients that are undergoing CVVHD using low blood flows with a loading dose of 9 MU and a maintenance dose of 3 MU every 8 h (independent of body weight), so that therapeutic colistin concentrations have a high likelihood of being achieved.…”
Section: Discussionsupporting
confidence: 89%
“…Critically ill patients may develop acute or acute-on-chronic renal failure requiring a period of continuous renal replacement therapy (CRRT). Although pharmacokinetic (PK) studies and dosing recommendations for CMS in critically ill patients with normal or impaired renal function exist, there are only a few systematic studies of the pharmacokinetics of CMS and colistin in patients undergoing CRRT (10)(11)(12)(13). Dose recommendations in these patients therefore differ widely, and there is evidence that certain recommendations might lead to underdosing (14).…”
mentioning
confidence: 99%
“…Thus, based on these findings, also confirmed elsewhere (82,85), a CMS maintenance dose similar to or higher than that used in patients with preserved kidney function is needed to achieve adequate colistin C ss during CRRT (83,(86)(87)(88). A further study reported relatively high SA during CVVHDF (0.42 for colistin A and 0.48 for colistin B) with a high extent of colistin removal, suggesting the dose should not be reduced (89). In patients with septic shock and AKI undergoing coupled plasma filtration-adsorption/CVVHDF or hemoperfusion with polymyxin B fiber cartridges, colistin removal was high, especially in the case of coupled plasma filtration-adsorption/CVVHDF; however, the short duration of hemoperfusion probably resulted in very little impact on total-body colistin content (90).…”
Section: Polymyxinssupporting
confidence: 62%
“…These renal replacement modalities were shown to have a substantial impact on the plasma colistin concentration achieved from a given daily dose of CMS; this was in agreement with reports from case studies and case series. 54,[61][62][63][64][65][66] There are two reasons why renal replacement therapy has such a substantial impact on dosage requirements of CMS. First, the circulating plasma concentrations of CMS are considerably higher than those of formed colistin (►Figs.…”
Section: Intravenous Administration Of Cmsmentioning
confidence: 99%